Relationship of Anemia During Pregnancy With Education and Trimester of Pregnancy (Medical Forum Monthly, 2024)
Objective: To find out relationship of anemia during pregnancy with education and trimester of pregnancy. Study Design: Community based cross-sectional descriptive studyPlace and Duration of Study: This study was conducted in urban slum areas of Taluka Qasimabad, District Hyderabad during six months of studying period from 1st March 2011 to 31st August 2011.Materials and Methods: The total population residing in the study areas was twelve thousand two hundred and seven (12207). During the study period of six months, two hundred and fifty (250) pregnant women were enrolled for the study. Pregnant women during 2nd and 3rd trimester of pregnancy were included in the study. The data was collected by conducting interviews, filling of the pre-tested, structured questionnaire and by assessing anemia by determining the hemoglobin level in the enrolled pregnant women. The questionnaire was a close-ended one, filled by the principle researcher herself. It comprised of demographic information about woman, her family, trimester of pregnancy about her education. Every woman’s hemoglobin was determined by using Sahli’s Hemoglobinometer. Anemia in pregnancy according to WHO classified into mild anemia hemoglobin level in the range of 10.0-10.9 g/dl, moderate anemia hemoglobin level in the range of 7-9.9 g/dl and severe anemia hemoglobin level is <7 g/dl Results: The association of various factors (determinants) with anemia was analyzed by applying chi-squared test; the p-value of <0.05 was taken as the level of significance. Two hundred and thirty three pregnant women were anemic while only seventeen women (6.8%) were found non-anemic. Majority of the women i.e. 70% presented with moderate anemia (hemoglobin level 7.0-9.9Gm /dl) while severe anemia (hemoglobin level <7 Gm/dl) was recorded in 5.2% pregnant women. Among total studied women, one hundred and forty seven were illiterate and were having different levels of severity of anemia; moderate anemia was recorded in majority of them ie in 127 pregnant women. The educational level had strong association with occurrence of anemia as well as on its severity (p=0.00). Regarding trimester of pregnancy and the occurrence of anemia, out of 158 pregnant women presenting in their third trimester of pregnancies, 143 were moderately to severely anemic. Trimester of pregnancy and occurrence of anemia were found statistically significant. It was also associated with severity of anemia (p=0.00).Conclusion: Relationship of anemia during pregnancy with low level of education and trimester of pregnancy is very high residing in urban slum areas of Taluka Qasimabad, District Hyderabad is high. Current findings highlight the anemia in pregnancy, education and early booking during pregnancy as a priority area of concern.